Profil Tindak Lanjut Hasil Pengawasan Sarana Produksi Distribusi Obat dan Makanan dan Upaya Perbaikaannya - Bidan Tringani Damanik (Badan Pengawas Obat dan Makanan, 2022)
The inspection of production and distribution facilities carried out by the Balai POM in Ambon is said to be successful if the follow-up recommendations of the inspection results are followed up on time and in accordance with suggestions for improvement. The recommendations realization achievement for the results of inspections followed up by stakeholders in 2020 was 27.78% of the target of 55.00%. The average achievement in the last 3 (three) years is 37.80% of the average target of 51.67%. The trend of achieving follow-up recommendations for inspection results in the previous 3 (three) years tends to decrease. The follow-up profile review of recommendations for inspection results was prepared using descriptive analysis of secondary data compared to standards through systematic literature studies to provide information on alternative improvement strategies in the future. Increasing the follow-up of recommendations on the results of an inspection by stakeholders can be carried out through strategies to improve internal and external factors. Improvement of internal factors such as the timing of publishing and submitting recommendations for inspection results, communication patterns with stakeholders, planning inspection targets, and monitoring and evaluation. External factors improvements, including stakeholder understanding of the follow-up of recommendations on production and distribution facilities inspection results and its benefits for the regions. Monitoring, evaluating, and reviewing the cooperation agreements formed with the regency/city government in Maluku province. Refreshment of regulations on the effectiveness and follow-up of the results of drug and food control; and forming cooperation agreements with district/city governments that still need to have a cooperation agreement. Another improvement strategy is communication, information, and education to the public, who will be the end consumers of drug and food circulation. Sufficient and up-to-date knowledge and understanding are one of the capitals to becoming smart consumers to be more agile and selective in choosing and consuming the drugs and food needed.